Detecting small–scale horizontal gradients in the upper ocean using wavelet analysis. (5th October 2016) - North, Ryan P.; Riethmüller, Rolf; Baschek, Burkard
Abstract: Mesoscale and submesoscale eddies and fronts in the upper ocean are often closely coupled with biogeochemical processes. Improved instrumentation provides high–resolution data in both the horizontal and vertical capturing this large range of scales (1–100 km), but novel analysis methods are still needed to take full advantage of this advancement. A new method using wavelet analysis is therefore proposed to identify the horizontal scales at which biophysical interactions occur, defined by concurrent fluctuations in temperature and phytoplankton patchiness. The method is applied to temperature and chlorophyll–a fluorescence data measured in the North Sea's German Bight during early spring using a towed undulating vehicle. The wavelet analysis identified the scale and location of individual features characterized by horizontal gradients of temperature and chlorophyll–a fluorescence. Applied to multiple transects, the method can also retrieve the statistics of relevant biophysical scales in a particular region. The combined analysis of seven transects suggests that physical and biogeochemical tracers tend to align at scales of 3–15 km in the German Bight, highlighting the likely relevance of submesoscale processes in this region. In general, the proposed wavelet analysis method is shown to be a robust tool for the analysis of biophysical interactions across a range of scales. Highlights: Submesoscale features are often coupled with biogeochemical processes. Wavelet analysis can identify the horizontal scales of biophysical interactions. Defined by concurrent fluctuations in temperature and phytoplankton patchiness. In the German Bight, relevant scales of 3–15 km were identified. Potential of submesoscales as drivers of biophysical coupling in the German Bight.